2014
DOI: 10.1021/ac500578h
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Platform for Direct Capture and Analysis of Airborne Mycobacterium tuberculosis

Abstract: Airborne Mycobacterium tuberculosis is the main source of tuberculosis infection, which is known as one of the worldwide infectious diseases. Direct capture and analysis of airborne Mycobacterium tuberculosis is essential for disease prevention and control. At present, low concentration of pathogens directly collected from the air is the major drawback for rapid analysis. Herein an integrated microfluidic system capable of airborne Mycobacterium tuberculosis capture, enrichment, and rapid bacteriological immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 39 publications
0
44
0
2
Order By: Relevance
“…SK‐BR‐3 cells are dissociated by using 0.25% trypsin‐EDTA solution. As SK‐BR‐3 cells overexpress HER2 protein on the surface, the SK‐BR‐3 cells can be introduced to microbeads to perform the immunoreaction .…”
Section: Methodsmentioning
confidence: 99%
“…SK‐BR‐3 cells are dissociated by using 0.25% trypsin‐EDTA solution. As SK‐BR‐3 cells overexpress HER2 protein on the surface, the SK‐BR‐3 cells can be introduced to microbeads to perform the immunoreaction .…”
Section: Methodsmentioning
confidence: 99%
“…While Warkiani et al (2015) reported that shear-modulated inertial microfluidic was potential for malarial detection because its sensitivity is hundred times higher than the standard gold-microscopy method [46]. Direct capture and analysis of infected airborne with Mycobacterium tuberculosis in less than 1 h has been also achieved by using a microfluidic platform [47].…”
Section: Biomedical Assaymentioning
confidence: 99%
“…All the negative samples (1)(2)(3)(4)(5) are detected to be negative using C-mode GLFT and ELISA. For positive samples (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), all the samples are detected to be positive by C-mode GLFT (Figure 7).…”
Section: Serum Samples Analysismentioning
confidence: 99%